Efficient and reusable ordered mesoporous WOx/SnO2 catalyst for oxidative desulfurization of dibenzothiophene. Issue 44 (13th August 2021) - Piao, Wenxiang; Li, Zhenghua; Li, Chengbin; Park, Jin Seo; Lee, Jung-ho; Li, Zhengyang; Kim, Ki Yeong; Jin, Long Yi; Kim, Ji Man; Jin, Mingshi
Abstract : The highly ordered mesoporous WO x /meso-SnO2 showed excellent catalytic activity and reusability in removing dibenzothiophene (DBT). Abstract : The oxidative desulfurization (ODS) of organic sulfur compounds over tungsten oxide supported on highly ordered mesoporous SnO2 (WO x /meso-SnO2 ) was investigated. A series of WO x /meso-SnO2 with WO x contents from 10 wt% to 30 wt%, were prepared by conventional wet impregnation. The physico-chemical properties of the WO x /meso-SnO2 catalysts were characterized by X-ray diffraction (XRD), N2 adsorption–desorption isotherms, electron microscopy, Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, and the temperature-programmed reduction of hydrogen (H2 -TPR). The characterization results indicated that these catalysts possessed mesoporous structures with uniform pores, high specific surface areas, and well-dispersed polyoxotungstate species on the surface of meso-SnO2 support. The ODS performances were evaluated in a biphasic system (model oil/acetonitrile, S initial = 2000 ppm), using H2 O2 as an oxidant, and acetonitrile as an extractant. Dibenzothiophene (DBT) in the model oil was removed completely within 60 min at 50 °C using 20 wt% WO x /meso-SnO2 catalyst. Additionally, the effect of reaction temperature, H2 O2 /DBT molar ratio, amount of catalyst and different sulfur-containing substrates on the catalytic performances were also investigated in detail. More importantly, the 20 wt% WO x /meso-SnO2 catalyst exhibited 100% surfur-removal efficiency without any regeneration process, even after six times recycling.